Factors affecting grief adjustment - Flatt, Bill (Journal of religion and health, 1988)
Earlier research has suggested that therapy and time are factors of change in grief level for those who are grieving. This follow-up study of widows and widowers suggests that there are also other relevant factors such as church activities, death of other relatives, other activities, time of grief counseling group, health, age, consideration of remarriage, religion, number of months widowed, and financial situation. A regression analysis of 138 widows and widowers found each of these factors significantly related to the. 05 critical level of significance to various measures of grief level.